The use of vibration characteristic to update the structure model - Pham Xuan Khang (Vietnam Journal of Mechanics)
Many authors studied algorithms adjusting the structure model based on modal data. This paper proposes an algorithm to detect the structure model using correlation factors between experimental and theoretical modal data in a damage library. The result from an experiment on 1-40 bridge (New Mexico USA) is presented to illustrate.